2019
DOI: 10.1093/mnras/stz1482
|View full text |Cite
|
Sign up to set email alerts
|

Blazar Mrk 501 shows rhythmic oscillations in its γ-ray emission

Abstract: Quasi-periodic oscillations (QPO) originating from innermost regions of blazars can provide unique perspective of some of the burning issues in blazar studies including disk-jet connection, launch of relativistic jets from the central engine, and other extreme conditions near the fast rotating supermassive black holes. However, a number of hurdles associated with searching QPOs in blazars e.g., red-noise dominance, modest significance of the detection and periodic modulation lasting for only a couple of cycles… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 59 publications
2
39
1
Order By: Relevance
“…Both blazars are known to exhibit extreme variability, which could be caused by a number of processes. Recently, hints of a quasi periodic oscillation (QPO) of Mrk 501 with a period of about 322 days have been found with Fermi-LAT at GeV energies featuring global and local significances of the signal above 99% [4]. Observing such QPOs also in the TeV-range for Mrk 421 or Mrk 501 would lead to a better understanding of the variability of AGN.…”
Section: Introductionmentioning
confidence: 99%
“…Both blazars are known to exhibit extreme variability, which could be caused by a number of processes. Recently, hints of a quasi periodic oscillation (QPO) of Mrk 501 with a period of about 322 days have been found with Fermi-LAT at GeV energies featuring global and local significances of the signal above 99% [4]. Observing such QPOs also in the TeV-range for Mrk 421 or Mrk 501 would lead to a better understanding of the variability of AGN.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the hunt for periodic signals in blazar light curves has become an active field of research: blazar OJ 287 is famous for its ∼12-year periodicity detected in its historical optical light curve [6,7] and another famous source PG 1553 + 113 is found to show 2.18-year periodic modulations in its γ-ray observations from the Fermi/LAT, which was first reported in [8]. In addition, several authors have reported the existence of QPOs of various characteristic timescales in numerous blazar multi-frequency light curves including the four cases of QPO detection by our research group see [4,[9][10][11] and the references therein.…”
Section: Introductionmentioning
confidence: 55%
“…The analyses revealed an underlying sub-year timescale (332 d) γ-ray QPO that persisted nearly 7 cycles. Applying PSRESP analysis the significance of the detection was found to be above 99% against possible spurious detection for details see [11]. • J1043+2408: A ∼ 560-d QPO was detected in the radio (15 GHz) observations of the BL Lac source J1043+2408.…”
mentioning
confidence: 98%
“…Curiously, the FACT monitoring of another bright blazar Mrk 501 has revealed a hint of quasi-periodic behaviour with a period of 332-days [5]. Even while no statistical significance of the hint, or possible systematics effects have been evaluated yet, it is interesting to note that a similar period has been obtained in the analysis of Fermi-LAT data of the same source [58].…”
Section: Pos(icrc2019)031mentioning
confidence: 78%